Acute Diacetylmorphine (Heroin) Intoxication (Review) - A. T. Loladze; G. A. Livanov; B. V. Batotsyrenov; A. L. Kovalenko; A. N. Lodyagin; S. I. Glushkov; D. V. Baranov; A. M. Antonova; T. V. Kharitonova (Общая реаниматология)
This review presents current data on the mechanism of action, selective toxicity, toxicokinetics and toxicodynamics of diacetylmorphine (heroin). Acute diacetylmorphine poisoning is considered under taking into account the developing a critical state, in which the poisoning severity is determined by severe metabolic disorders associated with the progression of hypoxia. The main lifethreatening complications of acute diacetyl morphine poisoning are described including those associated with the nervous system, respiratory, circulatory and urinary systems. Since hypoxia is the principal damaging factor, the the mechanisms of oxygen transport disorders and the pathogenesis of activation of free radical oxidation in acute diacetylmorphine poisoning are discussed. The improvement of intensive care strategy for severe forms of acute diacetylmorphine poisoning by the inclusion of a substrate antihypoxant Reamberin into the list of routine critical care prescriptions is emphesized.